Community-Acquired Pneumonia in the Asia-Pacific Region - Song, Jae-Hoon; Huh, Kyungmin; Chung, Doo Ryeon (Seminars in Respiratory and Critical Care Medicine, 2016)
Community-acquired pneumonia (CAP) is an important cause of mortality and morbidity worldwide. Aging population, dense urbanization, and poor access to health care make the Asia-Pacific region vulnerable to CAP. The high incidence of CAP poses a significant health and economic burden in this region. Common etiologic agents in other global regions including Streptococcus pneumoniae, Mycoplasma pneumoniae, Haemophilus influenzae, Chlamydophila pneumoniae, Staphylococcus aureus, and respiratory viruses are also the most prevalent pathogens in the Asia-Pacific region. But the higher incidence of Klebsiella pneumoniae and the presence of Burkholderia pseudomallei are unique to the region. The high prevalence of antimicrobial resistance in S. pneumoniae and M. pneumoniae has been raising the need for more prudent use of antibiotics. Emergence and spread of community-acquired methicillin-resistant S. aureus deserve attention, while the risk has not reached significant level yet in cases of CAP. Given a clinical and socioeconomic importance of CAP, further effort to better understand the epidemiology and impact of CAP is warranted in the Asia-Pacific region.
Keywords: community-acquired pneumonia; Asia-Pacific; epidemiology; antimicrobial resistance; socioeconomic impact